Religious Guidance Strategy in Overcoming the Boredom of Orphanage Children - Chairunnisa, Fany; Saburi, Annai (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study aims to reveal how the strategy of religious guidance given by caregivers in overcoming child boredom at the Al-Jam'iyatul Washliyah Orphanage Medan. The method used in this research is qualitative research with a case study approach. Data collection techniques were carried out through interview guidelines, observation guidelines, and documentation. The research subjects were the head of the orphanage, the caretakers of the orphanage, and the children at the Al-Jam'iyatul Washliyah Orphanage. To analyze the data, the researcher used interview transcripts, data reduction, analysis, and interpretation of data, and then conclusions were drawn from the data. Based on the results of the analysis, it was concluded that the religious guidance strategy carried out by caregivers at the Al-Jam'iyatul Washliyah Orphanage Medan, namely carrying out routine lectures carried out in rotation, carrying out "words of advice" activities which are carried out two times a week, and providing adequate extracurricular activities so that it can overcome the boredom of foster children while in the orphanage.